FRI0276 Prevalence of depression by beck ii and importance of fatigue by facit iv questionnaires in systemic lupus erythematosus patients vs controls in a single center of argentina. (15th June 2017) - Avid, E; Braillard-Poccard, A; Carrasco, M Garcia; Perez, N; Nasswetter, G; Dubinsky, D
Abstract : Background: Estimated prevalence of neuropsychiatric symptoms in SLE is among 17 to 71% 1 . Depressive symptoms are around 54% 1, 2 . Fatigue is frequently referred, predicts high morbidity and may be influenced by lifestyle and individual psychological characteristics 1 . Objectives: To evaluate the prevalence of depressive symptoms and its association with demographics and clinical variables in patients with SLE. To determine the predictive value of FACIT for fatigue in SLE vs controls. Methods: Observational, retrospective case- control design. Patients ≥18 years old with SLE (ACR 97) were consecutively evaluated in our centre from January to July 2015. We analyzed age, disease duration, clinical manifestations, antibodies profile, SLEDAI (≥4 scored as active) and SLICC. We recorded familiar psychiatric diseases, educational and socioeconomic level (Graffar Scale), employment and marital status. Beck II and FACIT (IV version) questionnaires were used for evaluate depression and fatigue respectively. We tested two cut points for fatigue:<22 and<40 to determine sensitivity/specificity for this tool in SLE patients vs controls 3 . Continues data were compared using t Student and Mann Whitney. Categorical data: chi-square or Fisher's exact test by SPSS version 20.0. To predic fatigue we calculated the area under the curve by Receiver Operating Characteristic (ROC). Statistical significant= p<0.05. Results: 77 SLE and 100 controls, all female. SLE vs control group: Mean of age ys: 34 (19–49)vs 38 (19–60). Prevalence of depression: 52% (44/77) vs 29% (29/100) (p<0.05). Prevalence of fatigue (FACIT<40): 42% (33/77) and 36% (36/100) (p>0.05). Mean disease duration (months) 48 (24–114). Socio-demographic characteristics, SLICC/SLEDAI, clinical and serological manifestations were not correlated with major depression p>0.05. FACIT: Median value: 31 (range 22–40) SLE group. FACIT<22 total SLE: 12/77 (15%) and FACIT<40: 33/77 (42%). Cut points FACIT SLE vs controls: <22: 15% (12/77) vs 1% (1/100) (p<0.05), 30% sensitivity/100% specificity, 100% PPV and 57% NPV. AUC FACIT <22: 0.65 (0.65–0.77). FACIT<40 in SLE vs controls: 42% (33/77) vs 26% (26/100) (p<0.05), 69% sensitivity and 84% specificity, 82% PPV and 70% NPV. AUC FACIT<40: 0.75 (0.64–0.87). Conclusions: Prevalence of depression was high in our cohort and similar to previously reported 1 . Our patients showed low levels of SLEDAI/SLICC. There was not relation between activity levels and baseline damage with the presence of depression 4 . FACIT IV scale was a good independent predictor of fatigue in SLE patients with or without depression vs controls. References: L Palagini M et al Depression and systemic lupus erythematosus: a systematic review. Lupus 2013. Hugo FJ et al DSM-III-R classification of psychiatric symptoms in systemic lupus erythematosus. Psychosomatics 1996. Lai JS et al Validation of the Functional Assessment of Chronic Illness Therapy-Fatigue Scale in Patients with Moderately to Severely Active Systemic Lupus Erythematosus, Participating in a Clinical Trial Journal of Rheumatology 2011. Segui J et al Psychiatric and psychosocial disorders in patients with systemic lupus erythematosus: A longitudinal study of active and inactive stages of the disease. Lupus 2000. Disclosure of Interest: None declared